2015
DOI: 10.1080/02640414.2014.1003586
|View full text |Cite
|
Sign up to set email alerts
|

The influence of elbow joint kinematics on wrist speed in cricket fast bowling

Abstract: This modelling study sought to describe the relationships between elbow joint kinematics and wrist joint linear velocity in cricket fast bowlers, and to assess the sensitivity of wrist velocity to systematic manipulations of empirical joint kinematic profiles. A 12-camera Vicon motion analysis system operating at 250 Hz recorded the bowling actions of 12 high performance fast bowlers. Empirical elbow joint kinematic data were entered into a cricket bowling specific "Forward Kinematic Model" and then subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…This creates a trade-off between the two and an optimal recoil percentage exists for each peak elbow hyperextension in order to maximise the gain in ball speed (Figure 4). The increase in ball speed of non-recoiling elbow hyperextensions over a straight arm disagrees with the results found by Middleton et al (2015) which indicated that an elbow with a fixed offset in hyperextension bowled slower than a straight arm. It is proposed that an increase in ball speed is always possible with a flexion/extension and/or abduction/adduction offset as long as the orientation of the upper arm increases the ability for the shoulder to do work as suggested by Marshall and Ferdinands (2003).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This creates a trade-off between the two and an optimal recoil percentage exists for each peak elbow hyperextension in order to maximise the gain in ball speed (Figure 4). The increase in ball speed of non-recoiling elbow hyperextensions over a straight arm disagrees with the results found by Middleton et al (2015) which indicated that an elbow with a fixed offset in hyperextension bowled slower than a straight arm. It is proposed that an increase in ball speed is always possible with a flexion/extension and/or abduction/adduction offset as long as the orientation of the upper arm increases the ability for the shoulder to do work as suggested by Marshall and Ferdinands (2003).…”
Section: Discussioncontrasting
confidence: 56%
“…It is proposed that an increase in ball speed is always possible with a flexion/extension and/or abduction/adduction offset as long as the orientation of the upper arm increases the ability for the shoulder to do work as suggested by Marshall and Ferdinands (2003). Previous research investigating the effect of flexion or extension of the elbow from upper arm horizontal to ball release has found differing results where both flexion (Middleton et al, 2015) and extension (Portus et al, 2006;Roca et al, 2006) have been shown to increase ball speed. The results in this study show that a greater increase in ball speed is caused by the recoil (mechanism 2) than extension to peak hyperextension (mechanism 1) which agrees with Middleton et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations